A review of bamboo biochar as an adsorbent for contaminations removal technology in wastewater treatment / Nur Ainiah Haron - Haron, Nur Ainiah (2022)
Bamboo biochar is a stable carbon-rich material, that encompasses enormous promise for dealing with wastewater pollutants. Its purpose is in developing recognition due to the ease of production, the availability of feedstock, and the improved physicochemical qualities. Biochar's ability to depollute organic and inorganic pollutants is determined by its surface area, pore size distribution, surface functional groups, and the size of the molecules to be removed, whereas its physical architecture and surface properties are ascertained by the nature of the feedstock and the preparation method or conditions. Biochar has a wide range of potential applications in the realm of wastewater treatment. Biochar is utilized as a filter media for the removal of heavy metals and other contaminants. This paper discusses several approaches to the modification of bamboo as excellent biochar, as well as the effectiveness of bamboo-based adsorbents. Finally, this research review also investigates the points of view of biochar technology and a few recommendations for future development possibilities in wastewater treatment.